STABLE CLUSTERING ON AODV WITH SLEEP MODE - Malhotra, Prerna; Dureja, Ajay (European Scientific Journal, ESJ, 2013)
Clustering has evolved as an imperative research domain that enhances system performance such as throughput and delay in Mobile Ad hoc Networks (MANETs) in the presence of both mobility and a large number of mobile terminals. In this thesis, we present a clustering scheme that minimizes message overhead and congestion for cluster formation and maintenance. The algorithm is devised to be dependent on Ad-hoc On Demand Distance Vector (AODV) Routing with sleep mode algorithm of MANET. The dynamic formation of clusters helps reduce data packet overhead, node complexity and power consumption. The goal of this algorithm is to decrease the number of cluster forming, maintain stable clustering structure and maximize lifespan of mobile nodes in the system. Nodes in MANET networks are basically battery operated, and thus have access to a limited amount of energy. This process proposes an Energy based Ad-Hoc on-Demand Routing algorithm that balances energy among nodes so that a minimum energy level is maintained among nodes and the lifetime of network is increased. The simulation has been performed in ns-2. The simulation shows that the number of clusters formed is in proportion with the number of nodes in MANET.